The Brexit vote and labour demand: evidence from online job postings - Javorcik, B; O'Kane, L; Kett, B; Stapleton, K (University of Oxford, 2019)
This paper uses high frequency data on the universe of job adverts posted online in the UK to study the impact of the trade uncertainty caused by the Brexit referendum on labour demand. We develop measures of industry and regional exposure to the threat of poten tial most-favoured-nation (MFN) tariffs if the UK were to leave the EU without a trade deal. We show that industries and regions more exposed to the tariff threat differentially reduced online hiring in the period after the referendum. We also show that the magni tude of this negative effect varied with the time-varying perceived probability of a no-deal Brexit, proxied by the relative frequency of Google-searches for terms associated with a no-deal Brexit. The policy implications of this paper are that uncertainty around trade policy, not only enacted policy, have real economic impacts and governments should therefore strive for clarity and predictability in their actions to create a strong enabling environment for the private sector.